Nanoherbal from Ethanol Extract of Dutch Teak Leaves (Guazuma ulmifolia Lamk.) and Antibacterial Potential Against Echerichia coli - Widya Dwi Larasati; Suyatno Sutoyo; Radita Yuniar Arizandy; Wahyu Setyarini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Guazuma ulmifolia Lamk. leaves, commonly known as Dutch teak leaves, are a medicinal plant traditionally used to treat diarrhea, infections, obesity, diabetes, and hypertension. Dutch teak leaves contain secondary metabolite compounds, including alkaloids, flavonoids, saponins, steroids, triterpenoids, tannins, phenolics, and glycosides. The presence of these compounds suggests that Dutch teak leaves have potential antibacterial activity. Herbal extracts have a limitation: low bioavailability. Therefore, nanoherbal formulations are used to improve their bioavailability. Nanoherbal is a nanoparticle made from plants. Nanoherbal can increase the surface area of medicinal herbs, thereby enhancing the solubility of compounds in the body. This study aims to determine the characteristics of nanoherbal derived from the ethanol extract of Dutch teak leaves and its antibacterial activity against Escherichia coli. The nanoherbal was synthesized using the ionic gelation method, employing alginate as the polyelectrolyte polymer and calcium chloride (CaCl₂) as the crosslinking agent. Four CaCl₂ concentrations were used: F1 (0.005%), F2 (0.01%), F3 (0.02%), and F4 (0.03%). Nanoherbal characterization, including particle size, zeta potential, and functional groups. The optimal nanoherbal formulation (F4) exhibited a particle size of 314.06 nm, a polydispersity index (PDI) of 0.0990, and a zeta potential of -131 mV. The FTIR spectra of nanoherbal showed a decrease in transmittance in the O-H, symmetric, and asymmetric COO- bands. The antibacterial activity was evaluated using the disc diffusion method. All treatments were conducted in triplicate, and results were expressed as average inhibition zone diameters (mm) and analyzed descriptively. The antibacterial activity test showed that the synthesized nanoherbal exhibited very strong activity against Escherichia coli, with an inhibition zone diameter of 23.65 mm. The synthesized nanoherbal showed a larger inhibition zone compared to the extract and alginate.